Functional properties of Corchorus olitorius L. Hydrocolloid in food model systems - Leonor, Janelle Lyn D.; Rumbaoa, Rowena Grace O. (Quezon City College of Home Economics, University of the Philippines Diliman, 2013)
The hydrocolloid from dried leaves of Corchorus olitorius L., commonly known as saluyot, was extracted and precipitated using boiling water and ethanol, respectively. Varying boiling times (30, 45 and 60 min) for hydrocolloid extraction were investigated. Results showed that the degree of esterification (DE) and viscosity of the extracted hydrocolloid were significantly (p < 0.05) affected when the boiling time was varied. The optimum boiling time was established at 45 min since there was no significant (p > 0.05) added benefit observed in terms of yield, DE and viscosity when the leaves were boiled beyond this time. At this boiling time, a hydrocolloid with 5.53% yield, 92.66% DE and 339.33 cP viscosity (of 1.0% hydrocolloid solution) was extracted. The hydrocolloid from C. olitorius L. was incorporated into food model systems to determine its functional properties and possible applications in food. Results showed that the hydrocolloid can produce very viscous solutions. However, it was observed that its viscosity was significantly affected by high temperatures and low pH. Results also showed that the hydrocolloid was not able to produce gels in the presence of high concentrations of sugar and acid and it also exhibited low emulsifying activity ranging from 4.99 to 7.03%. As delineated above, C. olitorius L. hydrocolloid can be a potential thickening ingredient in food although further research should be conducted in order to fully explore its potential.
Thesis (B.S. Food Technology)--University of the Philippines Diliman.
Keywords: Tossa jute -- Philippines; Hydrocolloid